MENGEMBANGKAN LITERASI SAINS MELALUI PENERAPAN E-PORTOFOLIO BERBASIS WEB BLOG UNTUK MENINGKATKAN KARAKTER KRITIS MAHASISWA CALON GURU SD - Arfilia Wijayanti; Riris Setyo Sundari; Ferina Agustini (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2016)
Scientific literacy is one of the important aspects that must be mastered PGSD students, because the effect on many aspects of science in life. The aims of the study are to identify initial level scientific literacy of PGSD students through the development of e-portfolio web blog based to improve students' critical character primary teachers candidate. The instruments used were a matter of scientific literacy test, questionnaire, and observation sheet. Data processing technique involves determining the level of scientific literacy, critical character observation of students, student questionnaire responses, as well as the analysis and conclusions. Based on the results of research and data analysis concluded that the ability of early scientific literacy in students who become the subject of research is still at the two-level categories of the four categories of scientific literacy are nominal and functional. The results of the field test analysis demonstrated ability scientific literacy of students more in nominal categories in the percentage range of 49% - 54%, the percentage of functional categories in the range of 34% - 44%, and a small part on procedural categories, namely 2%. Authentic Assessment Implementation of E-Portfolio Web Blog Based developed can enhance students' critical character effectively. Every aspect of critical character indicators of students has increased. Overall improvement (gain) student critical character of 0.83, which means the increase with higher criteria.Keywords: Authentic Assesment, E-Portofolio, Science Literacy, Critical Character